Reflections on the Relationship Between Cybernetic Pedagogy, Cognitive Science & Language - Aberšek, Boris; Dolenc, Kosta; Aberšek, Metka Kordigel; Pisano, Raffaele (Pedagogika, 2014)
Based on our previous educational researches we discuss whether it is possible to replace a human teacher with a virtual (machine) teacher, refereeing the hidden layers of doing so, as well as considering the technological possibilities currently available explain what this means in a society. For, an adaptation of current cybernetic into cybernetic pedagogy as cognitive modelling within a compounded educational system is proposed.